Environment Cultural Learning Model: A New Perception in Socio-Cultural-Based Environment History Learning - Deny Yudo Wahyudi; Daya Negri Wijaya; Heny Kusdiyanti; Shela Dwi Utari; Wiwik Astuti (Historia, 2026)
The purpose of this study is to describe a new learning model for teaching environmental history based on a sociocultural approach. This research employs a qualitative design, in which questionnaires were distributed to history teachers to collect data. The analysis process was conducted in three stages: data reduction, data display, and conclusion drawing. The result of this study is the development of a new learning model referred to as Environment Cultural Learning. This model has a syntax consisting of five stages: exploration, contextualization, application, collaboration, and reflection. The findings indicate that no specific model has previously outlined environmental history along with sociocultural values. Therefore, this study aims to provide an innovative learning model to support teachers. The Environment Cultural Learning model can be applied in the teaching of environmental history by exploring the environment and identifying sociocultural values that can be taught to students. This model consists of five stages: exploration, contextualization, application, collaboration, and reflection.